Is Dept Relief in the Interests of Creditors? - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper considers a number of reasons-in addition to the 'incentives' argument-why debt relief could be to the advantage of creditors collectively. Principal reasons analyzed are based on the 'investment-capacity' and the 'default-forestalling' arguments. Debt relief is defined as reduction of the present value of the contractual debt. The paper thus provides an analytical basis for various debt relief proposals that do not require finance or guarantees from creditor governments and for the considerable amount of relief in the form of rescheduling and concerted lending that has already taken place. The free rider problem and the extent to which the market may overcome it is discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet